Ketogenic Diets and Cardio-Metabolic Diseases - Zhang, Weiyue; Guo, Xin; Chen, Lulu; Chen, Ting; Yu, Jiayu; Wu, Chaodong; Zheng, Juan (Frontiers in Endocrinology, 2021)
While the prevalence of cardio-metabolic diseases (CMDs) has become a worldwide epidemic, much attention is paid to managing CMDs effectively. A ketogenic diet (KD) constitutes a high-fat and low-carbohydrate diet with appropriate protein content and calories. KD has drawn the interests of clinicians and scientists regarding its application in the management of metabolic diseases and related disorders; thus, the current review aimed to examine the evidences surrounding KD and the CMDs to draw the clinical implications. Overall, KD appears to play a significant role in the therapy of various CMDs, which is manifested by the effects of KDs on cardio-metabolic outcomes. KD therapy is generally promising in obesity, heart failure, and hypertension, though different voices still exist. In diabetes and dyslipidemia, the performance of KD remain controversial. As for cardiovascular complications of metabolic diseases, current evidence suggest that KD is generally protective to obese related cardiovascular disease (CVD), while remain contradictory to diabetes and other metabolic disorder related CVDs. Various factors might account for the controversies, including genetic background, duration of therapy, food composition, quality and sources of KDs. Therefore, it’s crucial to perform more rigorous researches to focus on clinical safety and appropriate treatment duration and plan of KDs.